2021
DOI: 10.1142/s0217979221501976
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of ultrashort optical pulses in anisotropic optical media with carbon nanotubes

Abstract: In this paper, we investigate the evolution of electromagnetic waves in a nonlinear anisotropic optical medium with carbon nanotubes (CNTs). Based on Maxwell’s equation, an effective equation is obtained for the vector potential of the electromagnetic field, which takes into account different values of the velocity and polarization with two directions. The dependence of the pulse shape on the crystal type, as well as the angle between the electric field and the CNTs axis is revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Next, let's make a comparison with the case considered earlier for semiconductor CNTs of the zigzag [22] type, as well as for zigzag tubes with metallic conductivity (n, 0), when n is a multiple of 3 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Next, let's make a comparison with the case considered earlier for semiconductor CNTs of the zigzag [22] type, as well as for zigzag tubes with metallic conductivity (n, 0), when n is a multiple of 3 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Оптика и спектроскопия, 2022, том 130, вып. 12 Далее проведем сравнение с рассмотренным ранее случаем для полупроводниковых УНТ типа zigzag [22], а также для трубок zigzag с металлической проводимостью (n, 0), когда n кратно 3 (рис. 2).…”
Section: результаты и обсуждениеunclassified
“…In previous studies devoted to birefringence a strong spreading of the pulse was reported due to the presence of the second component of field polarization [10,11]. To stabilize the pulse, it is proposed to use external field pumping as an option to alleviate the unavoidable dissipative effects that lead to the damping of the pulse.…”
Section: Model and Basic Equationsmentioning
confidence: 99%
“…In this study, in addition to the multiphoton absorption, we also take into account optically anisotropic properties of nonlinear medium [10,11], i.e. the effect of the general polarization itself on the propagation of extremely short pulses.…”
Section: Introductionmentioning
confidence: 99%